Stay clean: direct steam exposure to manage biofouling risks. (May 2019) - Joyce, Patrick W.S.; Cuthbert, Ross N.; Kregting, Louise; Crane, Kate; Vong, Gina Y.W.; Cunningham, Eoghan M.; Dick, Jaimie T.A.; Coughlan, Neil E.
Abstract: Biofouling by marine organisms can result in a variety of negative environmental and economic consequences, with decontamination procedures remaining problematic, costly and labour-intensive. Here, we examined the efficacy of direct steam exposure to induce mortality of selected biofouling species: Mytilus edulis ; Magallana gigas ; Semibalanus balanoides ; Fucus vesiculosus ; and an Ulva sp. Total mortality occurred at 60-sec of steam exposure for M. edulis and juvenile M. gigas, at 30-sec for S. balanoides, while 300-sec was required for adult M. gigas . Application of steam reduced the biomass of F. vesiculosus and significantly reduced Ulva sp. biomass, with complete degradation being observed for Ulva sp. following 120-sec of exposure. Accordingly, it appears that steam exposure can cause mortality of biofouling organisms through thermal shock. Although preliminary, our novel and promising results suggest that steam applications could potentially be used to decontaminate niche areas and equipment. Highlights: Steam exposure can cause mortality and biodegradation through thermal shock. Direct exposure to steam caused total mortality of biofouling bivalve species. Complete mortality can be achieved with short exposure times of ≤60 sec. Larger-bodied bivalves, e.g. adult Magallana gigas, required longer exposure times. Steam significantly reduced the biomass of Ulva sp.